The impact of fiscal dominance on macroeconomic performance in Sierra Leone: A DSGE simulation approach - Mohamed Samba Barrie; Emerson Abraham Jackson (West African Journal of Monetary and Economic Integration, 2022)
This study delves into the repercussions of fiscal policies, particularly those marked by high expenditure financed by monetary means, on key macroeconomic indicators in Sierra Leone. Employing a Dynamic Stochastic General Equilibrium (DSGE) model, the analysis illuminates how shocks in one variable ripple through the entire economic system over time. The analysis indicates that high levels of domestic borrowing and monetary financing in the medium-term crowd out private-sector investment hurt growth, and reduce government tax revenues, thereby reducing the government's capacity to invest in public goods and services. Furthermore, it demonstrates that this phenomenon leads to an endless "borrow-to-finance-debts-expenditures spiral" and creates more debt, worsens macro conditions, and exacerbates fiscal dominance. The paper recommends that policymakers manage Sierra Leone's fiscal trilemma, i.e., high development spending needs, high debt burden, and a low revenue base, not by taking on more debt and relying on monetary financing, but rather by expanding the economy's export capacity, harmonizing fiscal expenditures, and gradually expanding the domestic revenue base. Moreover, to prevent fiscal dominance from becoming systemic in the medium to long term, the research also recommends adhering to the Bank of Sierra Leone 2019 Act, which permits the Bank to cover temporary government deficits at no more than 5% of actual domestic revenue, excluding private receipts in the previous year. In sum, this study underscores the intricate interplay between fiscal policies and macroeconomic stability in Sierra Leone, offering a roadmap for policymakers to navigate the complexities of fiscal and monetary dynamics in the pursuit of enduring economic prosperity.
Keywords: E3; E5; H6; O2; 330; Fiscal dominance; macroeconomic variables; Sierra Leone; DSGE framework; monetary financing